2014
DOI: 10.1098/rspb.2013.2683
|View full text |Cite
|
Sign up to set email alerts
|

The importance of invertebrates when considering the impacts of anthropogenic noise

Abstract: Anthropogenic noise is now recognized as a major global pollutant. Rapidly burgeoning research has identified impacts on individual behaviour and physiology through to community disruption. To date, however, there has been an almost exclusive focus on vertebrates. Not only does their central role in food webs and in fulfilling ecosystem services make imperative our understanding of how invertebrates are impacted by all aspects of environmental change, but also many of their inherent characteristics provide opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
163
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(172 citation statements)
references
References 79 publications
6
163
0
Order By: Relevance
“…This can be interpreted as natural noise having high amplitude levels at low frequencies with some degree of nonlinearity at different frequencies compared to anthropogenic noise. A wide range of invertebrates have adapted to detect particle motion at frequencies below 1 KHz (Morley et al 2014), and stimuli of higher frequencies have been shown to be less relevant in other animals such as fish (Popper and Fay 1993;Fay and Popper 2012). However, nonlinearities in acoustic phenomena have been shown to increase unpredictability and result in a heightened behavioural response in meerkats (Townsend and Manser 2011;Karp et al 2014), marmots (Blumstein and Récapet 2009), and red deers (Reby and Charlton 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be interpreted as natural noise having high amplitude levels at low frequencies with some degree of nonlinearity at different frequencies compared to anthropogenic noise. A wide range of invertebrates have adapted to detect particle motion at frequencies below 1 KHz (Morley et al 2014), and stimuli of higher frequencies have been shown to be less relevant in other animals such as fish (Popper and Fay 1993;Fay and Popper 2012). However, nonlinearities in acoustic phenomena have been shown to increase unpredictability and result in a heightened behavioural response in meerkats (Townsend and Manser 2011;Karp et al 2014), marmots (Blumstein and Récapet 2009), and red deers (Reby and Charlton 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of noise on insects has been largely overlooked (Morley et al 2014), despite the fact that insects are hugely diverse and comprise the vast majority of species worldwide (Mora et al 2011) and thus have a crucial role in trophic networks (Schoenly et al 1991). The impacts of underwater noise on aquatic insects are likely to have a stronger effect at a community level compared to vertebrates in freshwater ecosystems due to the great contribution of aquatic invertebrates to a wide range of ecosystem functions such as controlling algal populations, shredding leaf litter to form fine particulate organic matter (FPOM), promoting wood decomposition, and controlling other macroinvertebrate populations, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that human‐generated sound can detrimentally affect animal hearing, communication, movements, and foraging (Shannon et al., 2015; Slabbekoorn et al., 2010). However, it is difficult to translate these effects into meaningful predictions about individual fitness and population‐level consequences, (Morley, Jones, & Radford, 2014) because animals could possibly move away from sound sources, the disturbance may be transient and the animals could compensate to prevent long‐term impacts (Bejder et al., 2006). Therefore, it is imperative there are more experimental studies performed on organisms that can be tracked to investigate directly whether common sources of human‐generated sound disrupt behavior and/or reduce survival (Simpson et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the greatest focus to date has been on acoustic communication, but there has been a bias towards avian species and sexual signals in this regard (Morley et al, 2014;Read et al, 2014;Shannon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%